Attendance of Patients with ophthalmological problems about Eye Protection from UV/blue Light Radiation from Sun light and Electronic Devices in Sulaimani City - Salah Qadir Mahmood; Muhammad Babakir-Mina; Salar Ibrahim Ali; Abdulrahman M. Ibrahem; Bakhtyar Kamal Talabany (Kurdistan Journal of Applied Research)
Ultraviolet (UV) and blue light are affecting eyes during the daily time and may cause many eye’s problems and diseases. Therefore, this study aimed to explore the awareness of patients with ophthalmological problems on UV/blue light protection measures and to evaluate their knowledge and protection measures about radiation that emits from sun light and other electronic devices. It comprised a cross-sectional survey on a representative target population with eye diseases who visited the Shahid Aso Eye Hospital at Sulaimani city (sample size = 500). A special designed cross-sectional questionnaire was performed on a random sampling for data collection from 9th September 2017 to 1st January 2018. The statistical analysis was performed using SPSS version 22.0. There was an even distribution between male and female participants across the groups. The highest percentage of patients with light sensitivity was (79.6%) and the lowest percentage with eye injury was (7.8%). Most of participants had knowledge about the effects of UV/blue light on eye diseases by (52%), cataract (57.8%), glaucoma and red eye with percentage of (45.8%) and (43.4%) respectively. There was a significant difference for the males who were more game-player and using electronic devices like smartphone/tablet /iPad than females. There was a significant difference between male and female participants about the knowledge on harmful effects of radiation from electronic devices. Furthermore, only the patients with sun light sensitivity and cataract had a significant knowledge about harmful effects of radiation from electronic devices on human eyes. Finally, most of the patients with dry eyes, eye/lid infection and glaucoma and cataract had significantly more practices for taking visual breaks when using electronic devices. This study concluded that the patients with ophthalmological problems show a low level of knowledge and protection measurements on the harmful effects of UV/blue light on human eyes and radiation protection. Additionally, this study has discovered that sun protection measures are commonly inadequate among the participants and on a regular basis only a small portion of participants were used the sun protection requirements.